Competencies of lower-level community health centre leaders in annual health work planning and their influence on district performance in Busoga sub-region: A retrospective study - Kharim Mwebaza Muluya; Gangu David Muwanguzi; Abdulmujeeb Babatunde Aremu; Naziru Rashid; Irene Wananda; Jonah Fred Kayemba; Collin Ogara; Musa Waibi; John Francis Mugisha; Peter Waiswa (PLoS ONE, 2025)
Introduction Lower-level community health centres play a crucial role in the delivery of primary healthcare services, and the competencies of their leaders can significantly influence district performance. Annual health work planning in local governments faces implementation obstacles every year. This mostly affects lower-level community health centres in Busoga region. It is evidenced by late submission of annual health work plans to authorized offices and also these work plans are poorly made by lower-level community health centres in Busoga region. This prompted a retrospective study to understand the competencies of leaders in the lower-level community health centres in annual health work plan development. Objective The study assessed the influence of competencies of lower-level community health centre leaders in annual health work planning on the district performance in Busoga region. Methods A retrospective (case-control) study design was employed to understand health centre performance across various districts in Busoga sub-region. There was a comparison of performance between the worst performing (case) and best performing (control) districts in the region according to the Annual Health Sector Performance reports from 2017/18 financial year to 2021/2022. Leaders in the lower-level community health centres were recruited to participate in the study. Data was collected between 17th July, 2024 and 23rd August, 2024. Statistical analysis was conducted on data from 12 case health centres and 12 control health centres using STATA version 16 to determine competencies of lower-level community health centre leaders that influence district performance. Results The study found that the district performance in annual health work planning was poor in both the case and control groups (26.4% and 47.2% respectively). Only three competencies variables of lower-level community health centre leaders were significantly influencing the performance of the districts. Districts with health facilities which reported that their Health Unit Management Committees (HUMCs) were fully constituted as guided by their leaders for annual health work planning, had significantly higher odds (AOR = 13.551, 95% CI: 4.816–38.617, p < 0.001) and performed better than those whose HUMCs were not fully constituted. Additionally, districts with health facilities which indicated that Heads of Departments (HODs) were involved in the annual health work planning process had significantly higher odds (AOR = 6.500, 95% CI: 3.109–10.791, p = 0.007) of better planning outcomes. Furthermore, districts with facilities that organized annual planning meetings by their leaders had significantly increased odds (AOR = 3.060, 95% CI: 1.399–6.916, p = 0.002) of achieving effective planning and the performance of the district. Conclusion The competencies of lower-level community health centre leaders in fully constituting the health unit management committees, involving heads of departments in the annual planning processes and organizing annual meetings for effective planning, highly contributes to the general performance of districts in the Busoga sub-region. Strengthening these competencies through targeted supportive meetings, consistently appointing HUMC members in health centres and creation of active departments of health centres as initiatives are recommended to enhance the overall effectiveness of health service delivery in Busoga sub-region.